Functional effects of cardiac sympathetic denervation in neurogenic orthostatic hypotension - Imrich, Richard; Eldadah, Basil A.; Bentho, Oladi; Pechnik, Sandra; Sharabi, Yehonatan; Holmes, Courtney; Grossman, Ehud; Goldstein, David S. (Parkinsonism & related disorders, 2009)
Diseases characterized by neurogenic orthostatic hypotension (NOH), such as Parkinson disease (PD) and pure autonomic failure (PAF), are associated with cardiac sympathetic denervation, as reflected by low myocardial concentrations of 6-[ 18F]fluorodopamine-derived radioactivity. We studied the impact of such denervation on cardiac chronotropic and inotropic function. Cardiac inotropic function was assessed by the pre-ejection period index and the systolic time ratio index in response to the directly acting beta-adrenoceptor agonist, isoproterenol, and to the indirectly acting sympathomimetic amine, tyramine, in patients with PD + NOH or PAF (PD + NOH/PAF group, N = 13). We compared the results to those in patients with multiple system atrophy, which usually entails NOH with normal cardiac sympathetic innervation (MSA, N = 15), and in normal control subjects ( N = 5). The innervated and denervated groups did not differ in baseline mean pre-ejection period index or systolic time ratio index. Tyramine increased cardiac contractility in the MSA patients and controls but not in the PD + NOH/PAF group. For similar heart rate responses, the PD + NOH/PAF group required less isoproterenol ( p < 0.01) and had lower plasma isoproterenol levels ( p < 0.01) than did the MSA group. Among patients with NOH those with cardiac sympathetic denervation have an impaired inotropic response to tyramine and exaggerated responses to isoproterenol. This pattern suggests that cardiac denervation is associated with decreased ability to release endogenous norepinephrine from sympathetic nerves and with supersensitivity of cardiac beta-adrenoreceptors.